Characteristics of War Crimes in the Perspective of International Criminal Law - Dinda Ermiza; Muhammad Juwanda Arif; Zulfadly Siregar; T. Samsul Bahri; M. Agra Dwadima Putra (International Journal of Law, Social Science, and Humanities, 2025)
War crimes are offenses as defined in the Articles of International Law. To address war crimes in international law, there are different regulations, such as those set out in International Humanitarian Law (IHL), and within these regulations there are different areas of application. In addition to the Hague Convention, and jurisprudential conventions. The research uses normative legal research, namely research conducted on legal principles, legal rules in the sense of values (norms), concrete legal regulations and legal systems, which are related to the material under study. With the aim of discussing how the Characteristics of War Crimes in the Perspective of International Criminal Law. The results of this study War crime is one of the criminal acts that has not been fully accommodated into the rules of Indonesian national law. The applicable legal customs and regulations governing relations between kings are regulated through the law of nations. Ideally, war crimes are more dangerous than other types of international crimes